COVID-19 contagion concern scale (PRE-COVID-19): Validation in Cuban patients with type 2 diabetes - Caycho-Rodríguez, Tomás (2021)
ABSTRACT Aims It is important to have valid and reliable measures to determine the psychological impact of COVID-19 in patients with diabetes; however, few instruments have been developed and validated for this population. Therefore, the aim of this study was to validate the Scale of Worry for Contagion of COVID-19 (PRE-COVID-19) in a sample of patients with diabetes mellitus (DM). Materials and methods A total of 219 patients (66.2% female, mean age 58.5 SD = 18.2) participated, selected through non-probabilistic sampling. The PRE-COVID-19 and the Generalized Anxiety Disorder Scale-2 were applied. Reliability analysis was performed for internal consistency, structural equation modeling and item response theory modeling. Results The results show that a unidimensional 5-item model presents satisfactory goodness-of-fit indices and excellent reliability values. Likewise, convergent validity between the PRE-COVID-19 and a measure of anxiety is evident. All items present adequate discrimination parameters, allowing for discerning between those patients with critical concern about COVID-19 contagion from those with severe concern. Conclusion It is concluded that the PRE-COVID-19 is an instrument with adequate psychometric properties to measure concern about COVID-19 infection and the emotional impact in patients with DM.